2021
DOI: 10.1159/000520925
|View full text |Cite
|
Sign up to set email alerts
|

Early Appearance of Dendritic Alterations in Neocortical Pyramidal Neurons of the Ts65Dn Model of Down Syndrome

Abstract: Down syndrome (DS), which is due to triplication of chromosome 21, is constantly associated with intellectual disability (ID). ID can be ascribed to both neurogenesis impairment and dendritic pathology. These defects are replicated in the Ts65Dn mouse, a widely used model of DS. While neurogenesis impairment in DS is a fetal event, dendritic pathology occurs after the first postnatal months. Neurogenesis alterations across the lifespan have been extensively studied in the Ts65Dn mouse. In contrast, there is sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been suggested that cognition defects in different types of ID may be underpinned by alterations of different dendritic domains ( Granato and Merighi, 2022 ). In this connection it is interesting to note that dendritic branching defects in Ts65Dn pups mainly involve the basal domain shortly after birth (postnatal day 2) and the apical domain slightly later (postnatal day 8) suggesting a relationship between age, affected dendritic compartment ( Uguagliati et al, 2022 ) and, possibly, cognitive impairment in DS.…”
Section: Spatiotemporal Characteristics Of Neurodevelopmental Alterat...mentioning
confidence: 97%
See 3 more Smart Citations
“…It has been suggested that cognition defects in different types of ID may be underpinned by alterations of different dendritic domains ( Granato and Merighi, 2022 ). In this connection it is interesting to note that dendritic branching defects in Ts65Dn pups mainly involve the basal domain shortly after birth (postnatal day 2) and the apical domain slightly later (postnatal day 8) suggesting a relationship between age, affected dendritic compartment ( Uguagliati et al, 2022 ) and, possibly, cognitive impairment in DS.…”
Section: Spatiotemporal Characteristics Of Neurodevelopmental Alterat...mentioning
confidence: 97%
“…Recent evidence shows that granule neurons of Ts65Dn mice already exhibit dendritic hypotrophy and spine shape (but not density) alterations at postnatal day 8 ( Uguagliati et al, 2021 ). The presence of dendritic branching defects has been additionally found in neocortical pyramidal neurons of Ts65Dn pups aged 2 days ( Uguagliati et al, 2022 ). Taken together the latter two studies are in line with the early presence of dendritic alterations seen in infants with DS.…”
Section: Spatiotemporal Characteristics Of Neurodevelopmental Alterat...mentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, an apical and basal dendritic arbor is already detectable in neocortical pyramidal neurons at postnatal day (PD) 2, but the apical arbor is less well developed than the basal arbor [ 133 ]. Similarly, in rats, the basal and apical dendritic arbor of CA1 pyramidal neurons has a different time course; the number of basal dendrites is already established at the age of 5 days, while the lateral and terminal branches of the apical arbor emerge later [ 134 ].…”
Section: Fatty Acids and Neuron Maturationmentioning
confidence: 99%